2001
DOI: 10.1017/s0952523801181010
|View full text |Cite
|
Sign up to set email alerts
|

Early visual experience and the receptive-field organization of optic flow processing interneurons in the fly motion pathway

Abstract: The distribution of local preferred directions and motion sensitivities within the receptive fields of so-called tangential neurons in the fly visual system was previously found to match optic flow fields as induced by certain self-motions. The complex receptive-field organization of the tangential neurons and the recent evidence showing that the orderly development of the fly's peripheral visual system depends on visual experience led us to investigate whether or not early visual input is required to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 29 publications
5
25
0
Order By: Relevance
“…The diversity of neuron classes and their packing density have together constituted the major challenge faced by those researchers who would seek to identify wiring specificity in this or other regions of the fly's brain but are, we suggest, most easily tackled among the repeated neuronal arrays of a visual neuropil. Furthermore, some aspects of the optic lobe's deeper circuits depend little on the fly's visual experience (22,23), indicating that there, at least, the accuracy of synaptic wiring is inbuilt, making the medulla a clear candidate for neuronal stereotypy and an excellent test bed to examine both the accuracy with which neurons contact each other to form synaptic networks and, correspondingly, the accuracy of EM reconstructions used to catalog those networks.…”
Section: Significancementioning
confidence: 99%
“…The diversity of neuron classes and their packing density have together constituted the major challenge faced by those researchers who would seek to identify wiring specificity in this or other regions of the fly's brain but are, we suggest, most easily tackled among the repeated neuronal arrays of a visual neuropil. Furthermore, some aspects of the optic lobe's deeper circuits depend little on the fly's visual experience (22,23), indicating that there, at least, the accuracy of synaptic wiring is inbuilt, making the medulla a clear candidate for neuronal stereotypy and an excellent test bed to examine both the accuracy with which neurons contact each other to form synaptic networks and, correspondingly, the accuracy of EM reconstructions used to catalog those networks.…”
Section: Significancementioning
confidence: 99%
“…In fact, the dendritic spanning field of VS cells is unaltered in flies with genetically ablated eyes [122], and flies reared in the dark show no abnormalities in the receptive field organization of lobula plate cells [123]. Similarly, in the mammalian retina, where direction selectivity occurs independent of vision [for review, see 124], an intriguing subcellular topography has been reported for directionally tuned inputs on starburst amacrine cells [7].…”
Section: Deconvolution Of the Fluorescence Tracesmentioning
confidence: 99%
“…1a) [27, 29,30]. The sophisticated global patterns of preferred directions do not depend on visual experience and thus represent phylogenetic rather than developmental adaptations to optic-flow analysis [31]. The computation of self-motion based on optic flow is facilitated by the geometry of the compound eye lattice (Fig.…”
Section: Exploiting Global Features Of Optic Flow By Spatial Pooling mentioning
confidence: 99%